The Principle of Dominance and the Limitation of Changing the Use of Agricultural and Garden Lands - Nazari, Ali Akbar (2021)
The purpose of the present study was to investigate the principle of dominance and limitations imposed on changing the use of agricultural and garden lands. The former and latter are considered as important subjects continuously debated and discussed. Changing the use of garden and agricultural lands is a theoretically argued subject and is followed by the principal question of: how in the face of the dominance principle, the legal limitations in changing the use of agricultural and garden lands are justifiable? In terms of the method of study.the present research falls into the category of descriptive-analytic researches, and library studies have been conducted to answer the mentioned question. The results of the present study indicate that illegal change of use of agricultural lands is an obvious instance of conflict between personal and societal rights. Because the owner of an agricultural land, due to his/her personal rights is allowed to use the land in any legitimate and legal way he/she desires; however, the rights of the society and the future humans forbids the owner to use the land in ways that would harm the public/society. Based on the stated content, it is concluded that the ownership right is absolutely preserved for the real owner based on the principle of dominance, but in cases where this right is conflictual with societal rights, the societal rights would be counted prioritized over the former, and therefore it would be necessary to control personal rights. This preference has a clear and obvious instance in the context of changing the use of agricultural and garden lands; and it is rational that the society’s right will be dominant over the rights of the owner of agricultural and garden lands.